Quality Testing and Effectiveness Test of Organic Fertilizer at Simantri Ternak Sekar Pasti Wangi - Rukmini, Ni Ketut Sri; Sudewa, Ketut Agung; Nugraha, I Made Nanda Arya; Natama, I Putu Ngurah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The Community Partnership Program (PKM) is implemented as a form of community service to enhance the quality and effectiveness of organic fertilizer production by the Simantri Ternak Sekar Pasti Wangi group. This activity focuses on two main aspects: quality testing and effectiveness testing of solid and liquid organic fertilisers produced from livestock waste. Cows. The activity began with socialisation and discussions among members of the livestock farming group regarding the importance of standardising the quality of organic fertilisers. Next, fertiliser samples were taken for laboratory testing to determine the macro- and micronutrient content of the organic liquid fertilisers. In addition to quality testing, field effectiveness tests were also conducted by applying the fertilizer to plants. The test results showed that the organic fertilizer produced by the group has considerable potential in enhancing plant growth. However, several aspects require improvement, such as the levels of specific nutrients. The targets achieved in this activity are that partners understand and master the technique of making POC from 20% to 85%, partners are also expected to be able to apply POC to plants directly from the initial ability of 40% to 80%, partners can increase income by at least 25% by producing POC and reduce the use of chemical fertilizers by replacing it with urine sap POC. This activity can reduce environmental pollution by 95% through the processing of cow urine waste into an organic liquid fertilizer. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 3 – Good Health and Well-BeingSDG 6 – Clean Water and SanitationSDG 13 – Climate ActionSDG 15 –Life on Land